Role of ocean mesoscale structures in shaping the Angola-Low pressure system and the southern Africa rainfall - Desbiolles, F; Howard, E; Blamey, RC; Barimalala, R; Hart, NCG; Reason, CJC (Springer, 2020)
Southern African climate is under the influence of both tropical and subtropical systems which result in a complex region where important interactions co-exist over a large spectrum of spatiotemporal scales. The Angola Low (AL), situated on boundary between tropical and subtropical southern Africa, has been diagnosed as a key driver of moisture distribution in the region on daily to seasonal time scales. It has been demonstrated that the AL pressure system is sensitive to the dynamics of the neighbouring oceans, but to date no study has considered the model resolution of air–sea interactions required to simulate this sensitivity. Using sensitivity experiments with a regional atmospheric model, which differ only in the mesoscale sea surface temperature (SST) forcing characteristics (either the full spectrum of SST variability or only its large-scale components are included), we first quantify the importance of SST gradients on the AL strength and variability. The results suggest that the mesoscale SST variability of the Angola–Benguela Frontal Zone (ABFZ) plays a key role in AL activity, particularly during the late summer. Synoptic-scale tropical lows, which form the AL, are automatically detected, and the results suggest more extreme events occur when the model is forced by mesoscale SSTs (everywhere and in the ABFZ area only). The rainfall resulting from those events suggests that tropical-low episodes are associated with nearly 15% of the total rain in Angola and Namibia. The link between AL dynamics and wet spells is also discussed, with the former showing a different spatial pattern as well as frequency when the ocean is fully resolved.